AH-64 loss of lubrication study: test of isotropic superfinished AH-64 (Apache) engine nose gearbox without black oxide coating - Kane, T.; McKee, M.; Chhotu, P.; Peterson, J.; Thompson, G.; Rich, B.; Winkelmann, L. (My University, 2018)
Rotorcraft gearboxes are designed to the utmost precision to withstand the tremendous demand and loads required to convert thousands of horsepower and RPM into hundreds of RPM and lift torque. The transmission components and the lubricants utilized incorporate various technologies to enable proper function and longevity. Many of these technologies are "tried and true" over the course of hundreds of thousands of flight hours and decades of real flight experience. As a result, replacement of these legacy technologies requires a tremendous amount of testing and qualification. The US Dept. of Defense conducted a loss of lubrication test of an AH-64 Engine Nose Gearbox (ENGB) with Isotropic Superfinished (ISF) gears instead of the legacy black oxide coated gears. The question addressed in this paper is; will the low Ra value generated by Isotropic Superfinishing lead to scuffing, especially if the Black Oxide Coating is eliminated, and to go deeper, will the gearbox survive the mandatory loss of lubrication test requirements, which is a punishing test designed to simulate a realistic failure scenario within the gearbox. Success for this test is demonstrated by the ability of one gearbox to continue to transmit torque for 60 minutes after loss of lubrication, or of two gearboxes to continue to transmit torque for at least 30 minutes each after loss of lubrication. Upon successful completion of the loss of lubrication test, the gearbox was subjected to a detailed tear-down analysis which indicated no discernable damage occurred to the gear teeth.